Implications of Medicaid financing reform for state government budgets - Jeffrey Clemens; Benedic N. Ippolito (American Enterprise Institute (AEI), 2017)
We analyze potential reforms to Medicaid financing through the lens of fiscal federalism. Because substantial dollars are at stake, both the economic and political sides of intergovernmental transfers have high relevance in this setting. We show that changes in Medicaid financing formulas can shift amounts exceeding several hundred dollars per capita from "winning" states to "losing" states. In some cases, these amounts exceed 10 percent of states' own-source revenues. States' balanced budget requirements imply that such changes would, if not phased in gradually, require significant budgetary adjustment over short time horizons. We next show that alternative Medicaid financing structures have significant implications for states' exposure to budgetary stress during recessions. During the Great Recession, an acyclical block grant structure would have increased states' shortfalls by 2–3.5 percent of own-source revenues relative to either an explicitly countercyclical block grant or the current matching system. Finally, we assess the implications of several financing structures for the extent to which they subsidize states' decisions on both the "extensive" and "intensive" margins of coverage generosity over the short and long term.
Keywords: 330